FLUKTUASI NILAI KURS DAN INFLASI PENGARUHNYA TERHADAP EKSPOR IMPOR DAN NERACA PERDAGANGAN INDONESIA TAHUN 2007-2015 - Ida Bagus Gede Udiyana; Tettie Setiyarti (STIMI Handayani Denpasar, 2017)
The trade balance in the diffrerence or difference between export and import. If the value of the import was higher than export value then that happens in the deficit. Conversely, if the value of exports is higher than the imports value then that happens is the surplus. This study aim to know the influance of the fluctuation of the value of exchange rate and inflation against import export, and the influence of the fluctuation of the value of exchange rate , inflation and import export against trade balance. The hypotesis in this research is there is the influence of the exchange rate and inflation simultaneously against the import export and trade balance. The data used are the mountly data from the years 2007 – 2015 that consists of the data trade balance, exchange rate and inflation. The source of the data in this research are derived from documentation data bank of Indonesia and central bureau of statistik. Methods of analysis used is path analysis using SPSS. The results of this research found that the simultaneously rate and inflation is negative and significant effect against the import export, however partially, inflation has no effect against the import export, whereas the exchange rate effect towards import export. The result of this research also found that simultaneously inflation, exchange rate and export import is negative and significant effect against the trade balance, partially rate and inflation has no effect against the trade balance, whereas import export have significant influence towards trade balance.